Hydroxyapatite-Bioceramic/Expanded Perlite Hybrid Composites Coating on Ti6Al4V by Hydrothermal Method and in vitro Behavior - Muratoglu, Mehtap; Ozcan, Tugce (Sage Publications Ltd, 2023)
This study was aimed to coat a hybrid bioceramic composite onto Ti6Al4V by using hydrothermal method. The Hybrid bioceramic composite for coating was prepared by reinforcing different rations of expanded perlite (EP) and 5 wt.% chitosan into synthesized Hydroxyapatite (HA). Coating was performed at 1800 degrees C for 12 hours. The coated specimens were gradually subjected to a sintering at 6000 degrees C for 1 hour. For in vitro analysis, the specimens were kept in Ringer's solution for 1, 10, and 25 days. All specimens were examined by SEM, EDX, FTIR, and surface roughness analyses for characterizing. It was concluded that as the reinforcement ratio increased, there was an increase in coating thickness and surface roughness. The optimum reinforcement ratio for expanded perlite can be 10 wt.% (A3-B3). With increasing ratio of calcium (Ca) and phosphate (P) (Ca/P), the surface becomes more active in body fluid and then observed the formation of the hydroxycarbonate apatite (HCA) layer. As the waiting time increased, there was an increase in the formation of an apatite structure.
Keywords: Expanded perlite; hydroxyapatite; bioceramics; hydrothermal method